LA DOCTRINA MONROE: : 200 AÑOS DESPUÉS - García Bethancourth , Pantaleón (Cátedra, 2023)
This article evaluates the origins of the Monroe Doctrine, its purposes and its evolution from its origins to the present. It establishes that the criteria that the government of President Monroe took into account to make its declaration was the supposed danger of the Holy Alliance to invade the countries of Latin America, the presence of imperial Russia located in the northwestern region of North America and the expansionist ambitions of Great Britain in the same region. The paper maintains that the true purpose of Monroe’s declaration was to prevent the arrival of European powers in Latin America and prevent them from competing with the United States for raw materials and markets in the region. It also maintains that at the time of Monroe’s declaration there was no danger to Latin America and it was launched against an imaginary threat. Today, faced with the presence of other powers in the region such as China, Russia and Iran, the United States once again fanned the extra continental threat to continue maintaining its hegemony in the region.